Factorial Structure of the Teacher's Quality of Work Life Scale (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ABSTRACT:      The present research paper attempts to develop a valid and reliable measurement instrument that is designed to measure Quality Work Life (QWL) of elementary Algerian school teachers. This research relies on a questionnaire that includes 30 questions distributed to a sample that consists of 239 teachers. An exploratory factor analysis is applied to determine the number of factors of QWL. A confirmatory factor analysis is relied upon to verify the number of factors. To verify the validity and reliability of the device, a structural validity and a composite reliability are determined. The six significant factors are identified based on the factor analysis. Further analyses have revealed that these six factors together proved 64.55 % of the total variance.Keywords: measurement instrument; Quality of Work Life; factorial structure.  ملخص:      يهدف هذا البحث إلى تطوير أداة قياس صالحة وموثوقة مصممة لقياس جودة حياة العمل (QWL) لمعلمي المدارس الابتدائية الجزائرية. تكون المقياس من 30 فقرة تم تطبيقها على 239 معلمًا ومعلمة. تم إجراء تحليل العاملي استكشافي لتحديد عدد عوامل جودة حياة العمل. ثم إجراء تحليل العاملي التأكيدي للتحقق من عدد العوامل، للتحقق من صحة وموثوقية المقياس، تم تحديد الصلاحية الهيكلية والموثوقية المركبة، كما تم تحديد العوامل الستة الهامة بناءً على تحليل العوامل. أظهر التحليل الإضافي أن هذه العوامل الستة مجتمعة أوضحت 64.55٪ من التباين الكلي.كلمات دالة: أداة قياس؛ جودة حياة العمل؛ هيكل عاملي.